Outdoor Equipment Rental Information System on Vexa Adventure - Priyoatmoko, Wahyu; Ulinuha, Zakya Faaza; Kapti, Kapti; Fatkhurrochman, Fatkhurrochman; Yusnanto, Tri (International Journal of Computer and Information System (IJCIS), 2024)
Current technology has helped users in doing various things and activities that are able to produce the latest and innovative technology in various fields. Many people get convenience to meet their information and communication needs with the internet. The background of the creation of the Outdoor Equipment Rental Information System at Vexa Adventure Based on the Web is the processing of data that is still manual (reporting is done by bookkeeping every month) values that can be at high risk of damage and loss. The purpose of this study is to be able to design and build an outdoor equipment rental Information System at Vexa Adventure based on the web, using PHP - MySQL. And to find out the impact of implementing the system. The type of research used is engineering research with a research method using the Waterfall method. The stages of the waterfall method are Communication, Planning, Modelling, Construction, Deployment. The design used in this study is DFD (Data Flow Diagram) modelling which consists of four main components, namely data input, data output, data storage, and processes. The Flow of Document (FOD) is used to describe the ongoing procedure. The results of this study are in the form of a Web-Based Outdoor Equipment Rental Information System. The impact of implementing this system is proven by user evaluations using Likert scale calculations which show a value of 80%, which means the impact of implementing this system can help Vexa Adventure admins and owners in carrying out rental transactions. Hiking or also called nature trekking or tracking generally refers to a long and enthusiastic journey that usually passes through small roads in the interior. In Indonesia, this hike is identical to the journey to the top of the mountain. This activity is generally carried out by nature lovers clubs. Sometimes during the hike the journey must go through dense forest, and must cut bushes to make a path that can be passed. This hike can take more than 1 day of travel. The background to the creation of the Web-Based Outdoor Equipment Rental Information System at Vexa Adventure is the manual data processing (reporting is done by bookkeeping every month) values that can be at high risk of damage and loss. The purpose of this study is to be able to design and build a web-based outdoor equipment rental information system at Vexa Adventure, using PHP - MySQL. And to find out the impact of implementing the system. The type of research used is engineering research with a research method using the Waterfall method. The stages of the waterfall method are Communication, Planning, Modelling, Construction, Deployment. The design used in this study is DFD (Data Flow Diagram) modelling which consists of four main components, namely data input, data output, data storage, and process. The Flow of Document (FOD) is used to describe the ongoing procedure. The results of this study are in the form of a Web-Based Outdoor Equipment Rental Information System. The impact of implementing this system is proven by user evaluation using a Likert scale calculation which shows a value of 80%, which means that the impact of implementing this system can help Vexa Adventure admins and owners in making rental transactions.